Confocal Synaptology: Synaptic Rearrangements in Neurodegenerative Disorders and upon Nervous System Injury - Vulovic, Maja; Divac, Nevena; Jakovcevski, Igor (Frontiers in Neuroanatomy, 2018)
The nervous system is a notable exception to the rule that the cell is the structural and functional unit of tissue systems and organs. The functional unit of the nervous system is the synapse, the contact between two nerve cells. As such, synapses are the foci of investigations of nervous system organization and function, as well as a potential readout for the progression of various disorders of the nervous system. In the past decade the development of antibodies specific to presynaptic terminals has enabled us to assess, at the optical, laser scanning microscopy level, these subcellular structures, and has provided a simple method for the quantification of various synapses. Indeed, excitatory (glutamatergic) and inhibitory synapses can be visualized using antibodies against the respective vesicular transporters, and choline-acetyl transferase immunoreactivity identifies cholinergic synapses throughout the central nervous system. Here we review the results of several studies in which these methods were used to estimate synaptic numbers as the structural equivalent of functional outcome measures in spinal cord and femoral nerve injuries, as well as in genetic mouse models of neurodegeneration, including Alzheimer’s disease. The results implicate disease- and brain region-specific changes in specific types of synapses, which correlate well with the degree of functional deficit caused by the disease process. Additionally, results are reproducible between various studies and experimental paradigms, supporting the reliability of the method. To conclude, this quantitative approach enables fast and reliable estimation of the degree of the progression of neurodegenerative changes and can be used as a parameter of recovery in experimental models.